2020
DOI: 10.3892/mmr.2020.11748
|View full text |Cite
|
Sign up to set email alerts
|

hCINAP serves a critical role in hypoxia‑induced cardiomyocyte apoptosis via modulating lactate production and mitochondrial‑mediated apoptosis signaling

Abstract: acute myocardial infarction (aMi) is a major cause of heart failure and is associated with insufficient myocardial oxygen supply. However, the molecular mechanisms underlying hypoxia-induced cardiomyocyte apoptosis are not completely understood. in the present study, the role of human coilin interacting nuclear aTPase protein (hcinaP) in cardiomyocytes was investigated. ac16 cells were divided into the following four groups: i) Small interfering (si) rna-control (ctrl); (ii) sirna-hcinaP; (iii) empty vector; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Under OS conditions, MFN2 expression declines, whereas the protein related to mitochondrial fission, DRP1, elevates, leading to mitochondrial fragmentation, decreased energy metabolism, and ultimately mitochondrial apoptosis [ 31 33 ]. Our results indicated that hypoxia enhanced OS response, promoted mitochondrial apoptosis, and inhibited the metabolism of mitochondrial energy in H9C2 cells; these findings conform to those of previous studies [ 34 37 ]. However, the effects of hypoxia were weakened by the FAT10 overexpression.…”
Section: Discussionsupporting
confidence: 93%
“…Under OS conditions, MFN2 expression declines, whereas the protein related to mitochondrial fission, DRP1, elevates, leading to mitochondrial fragmentation, decreased energy metabolism, and ultimately mitochondrial apoptosis [ 31 33 ]. Our results indicated that hypoxia enhanced OS response, promoted mitochondrial apoptosis, and inhibited the metabolism of mitochondrial energy in H9C2 cells; these findings conform to those of previous studies [ 34 37 ]. However, the effects of hypoxia were weakened by the FAT10 overexpression.…”
Section: Discussionsupporting
confidence: 93%
“…Lysis buffer (Solarbio) was used to extract the protein from cells, followed by quantifying the protein content using a BCA protein quantitative kit (Beyotime Institute of Biotechnology, China). Western blots were performed according to standard procedures as previously described (Xie et al, 2021). Primary antibodies used in this study: anti‐actin (AC026; ABclonal), anti‐α‐SMA (19245; Cell Signaling), anti‐SMARCC1 (ab172638; Abcam), anti‐cytokeratin 8 (CK‐8) (ab53280; Abcam), anti‐cytokeratin 18 (CK‐18) (ab53280; Abcam), anti‐P‐MYPT (3040; Cell Signaling), anti‐MYPT (2634; Cell Signaling), anti‐RGS5 (NBP2‐249454; Novus Biologicals), anti‐SMMHC (A4064; ABclonal), anti‐RhoA (ab86297; Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…Two recent studies showed that cervical cancer cells exposed to hypoxia accumulated hCINAP in a HIF-1αdependent manner. Under hypoxic conditions, hCINAP both promotes epithelial-to-mesenchymal transition (EMT) by enhancing Akt/mTOR signaling and inhibits hypoxia-induced apoptosis [49,50]. hCINAP knockdown decreases hypoxia-induced lactate accumulation via regulated LDHA activity.…”
Section: The Transcription Of Hcinap Is Regulated By Hif-1α Under Hypoxiamentioning
confidence: 99%